2008
DOI: 10.1124/jpet.108.140293
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin, a Citrus Flavonoid, Improves Memory Impairment and Aβ Pathology in a Transgenic Mouse Model of Alzheimer's Disease

Abstract: Increasing evidence suggests that the elevation of ␤-amyloid (A␤) peptides in the brain is central to the pathogenesis of Alzheimer's disease (AD). Our recent studies have demonstrated that nobiletin, a polymethoxylated flavone from citrus peels, enhances cAMP/protein kinase A/extracellular signalregulated kinase/cAMP response element-binding protein signaling in cultured hippocampal neurons and ameliorates A␤-induced memory impairment in AD model rats. For the first time, we report that this natural compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
122
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(129 citation statements)
references
References 40 publications
2
122
1
1
Order By: Relevance
“…This test was applied as previously described (Onozuka et al, 2008). Briefly, mice were placed into the corner of a wooden box 50 X 50 X 40 cm and allowed to freely explore for 10 min.…”
Section: Open-field Testmentioning
confidence: 99%
“…This test was applied as previously described (Onozuka et al, 2008). Briefly, mice were placed into the corner of a wooden box 50 X 50 X 40 cm and allowed to freely explore for 10 min.…”
Section: Open-field Testmentioning
confidence: 99%
“…4 In addition, nobiletin has been found to exert antitumor activities, 5,6 to inhibit fulminant hepatitis, 7 and to improve memory impairment. 8 Although pharmacokinetic studies of nobiletin have been performed to examine the further characterizations of the metabolism and the biological effects of nobiletin, it have been carried out at relatively high dosage of nobiletin [9][10][11] since a sensitive analytical method has not been available. In order to discuss the realistic effects of nobiletin which, for example, are observed after daily beverage ingestion, an analytical method with high sensitivity is necessary for determining nobiletin in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vivo and in vitro studies have demonstrated the anti-inflammatory activities of nobiletin and its metabolites (Chen et al, 2007;Choi et al, 2007;Li et al, 2007;Murakami et al, 2000). Nobiletin helps to lower cholesterol levels (Whitman et al, 2005) and some studies indicate that it may improve impaired memory loss (Onozuka et al, 2008) and treat acne (Sato et al, 2007). Nobiletin has been shown to exhibit antitumor activities as indicated by the attenuation of pro-MMP-7 protein and its mRNA expression in HT-29 cells (Kawabata et al, 2005), down-regulation of leptin levels in mice with azoxymethane-and dextran sulfate sodium-induced colon carcinogenesis (Miyamoto et al, 2008), and the suppression of invasion and migration in human gastric adenocarcinoma AGS cells (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%